2013
DOI: 10.1128/jcm.02583-12
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Virulence Genes Detected by String PCR in Children from an Urban Community in Northeastern Brazil

Abstract: The accuracy of a nested PCR in gastric DNA obtained by a string test for the diagnosis of Helicobacter pylori infection in asymptomatic children was 94.0%. The cagA-positive toxigenic vacAs1m1 strains were the most prevalent strains, indicating that this population is colonized early by the strains associated with gastric cancer. Helicobacter pylori infection significantly increases the risk of development of peptic ulcer disease, distal gastric carcinoma, and gastric lymphoma (1). Infection of the general po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
(9 reference statements)
2
16
1
Order By: Relevance
“…The DNA was extracted directly from the gastric mucus/juice [obtained by the string procedure ( Gonçalves et al 2013 )] using the QIAmp kit (QIAGEN, Germany) according to manufacturer’s recommendations with minor modifications. The DNA concentration was determined by spectrophotometry using NanoDrop 2000 (Thermo Scientific, USA) and the samples were stored at -20ºC until use.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA was extracted directly from the gastric mucus/juice [obtained by the string procedure ( Gonçalves et al 2013 )] using the QIAmp kit (QIAGEN, Germany) according to manufacturer’s recommendations with minor modifications. The DNA concentration was determined by spectrophotometry using NanoDrop 2000 (Thermo Scientific, USA) and the samples were stored at -20ºC until use.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…Furthermore, with respect to the vac A i region, we are aware of only one study evaluating 11 symptomatic Bulgarian children ( Yordanov et al 2012 ). Previously, we have shown a high prevalence of infection by H. pylori strains carrying the cag A gene and the vac A s1 allele in asymptomatic children from northeastern Brazil, a high-risk area for gastric cancer, by evaluating gastric juice/mucus DNA obtained by a string test ( Gonçalves et al 2013 ). In this study, we aimed to characterise the number of CagA EPIYA motifs and the vac A i genotypes in H. pylori DNA from these children.…”
mentioning
confidence: 99%
“…Whether this is the case in asymptomatic children and/or whether it plays a role in persistence is unknown. Strains containing virulence-associated genes, cagA and the more virulent version of vacA (s1m1), have been documented in isolated samples of asymptomatic Brazilian and Colombian children, but it is unclear if these strains are associated with persistence [14,15].…”
mentioning
confidence: 99%
“…Ou et al [37] found that the fluorescent quantitative PCR test was more sensitive than conventional methods alone or in combination (p<0.01). A nested PCR had a sensitivity of 93.0% and a specificity of 100% compared with the 13 C-urea breath test (UBT) on gastric DNA obtained by a string test in asymptomatic children [2]. Baskovich et al [38] also detected a surprisingly high number of new cases with H. pylori by PCR, in both the normal biopsies and test cases, suggesting that PCR could detect colonization in asymptomatic patients.…”
Section: Molecular Methodsmentioning
confidence: 99%
“… found that the fluorescent quantitative PCR test was more sensitive than conventional methods alone or in combination (p<0.01). A nested PCR had a sensitivity of 93.0% and a specificity of 100% compared with the 13 C‐urea breath test (UBT) on gastric DNA obtained by a string test in asymptomatic children . Baskovich et al.…”
Section: Diagnosismentioning
confidence: 99%